Forrajeo de Didelphis pernigra (Mammalia: Didelphidae) en un área suburbana de la Sabana de Bogotá, Colombia - Barrera-Niño, Viviana; Sánchez, Francisco (THERYA, 2014)
Introduction: In Colombia, there is widespread transformation of natural ecosystems, especially in the Andean region. However, the impacts of those transformations have been poorly studied. Optimal patch theory was used to evaluate the foraging behavior and movement patterns in the white-eared opossum (Didelphis pernigra) in the Sabana de Bogotá, a plateau at about 2,600 m in the Colombian Andes. The study site was dominated by an exotic grass (Cenchrus clandestinum), and little is known about possible impacts of this exotic species on native fauna.Thus, we analyzed whether this grass the foraging behavior and movements of D. pernigra. To test this, we used the giving up density (GUD) technique, which uses the amount of food left in a feeding patch to assess the foragerâ€™s habitat perception. We also tested whether this exotic grassland acted as a barrier to movements to and from an area of native and exotic trees. Finally, we measured the influence of moon illumination, air temperature, and precipitation on the oppossumâ€™s foraging behavior. Methodology: We established two approximately parallel transects in a suburban area (Fig. 1). Foraging stations were located 30 to 40 meters apart on each transect. Each station consisted of a feeder made of a cylindrical plastic container with 150ml of sugar water in a 1:3 proportion. Each container also contained 60 glass spheres to generate diminishing returns on the harvest rate. The oppossums were habituated to the feeders for 15 days, and then GUDs were measured for 30 days. Feeders were filled before sunset and checked the following morning. Results: Oppossums foraged at least 240 m into the grasslands from the trees along the river. Air temperature and precipitation did not influence their foraging behavior (Fig. 2). There was, however, temporal variation in foraging activity, and at least some of this was due to a negative effect of lunar illumination (Fig. 3). Discussion and Conclusions: Our results indicate that the white-eared opossum is a tolerant species able to exploit human-created habitats. This finding is in agreement with reports on other species of Didelphis that they are tolerant of moderate human interventions. We surmise that this speciesâ€™ ability to exploit the open ecosystems of the paramo has made it possible for it to effectively use the grasslands on the study site. The only abiotic factor that was found to be influential was moon illumination. Darker nights gave lower GUDâ€™s indicating that the foragers perceived decreased predation risk. Finally, we argue that efforts should be made to prevent the local extinction of this opossum in disturbed areas of Bogotá since it could aid in the conservation of ecological functions in those areas. Key words: Andes, giving-up density (GUD), habitat selection, optimal patch use, urban ecology.